Association between Prosthesis Cleanliness and Patient’s Knowledge on Hygiene Habits among Complete Denture Patients and Partial Denture Prostheses Wearers - Basnyat, S KC; Mahanta, S; Sapkota, B (Journal of Nepalese Prosthodontic Society, 2022)
Introduction: To have good oral health of patients wearing denture they must maintain high standards of both oral hygiene and denture hygiene. The aim of this study was to access the level of knowledge on hygiene and prosthesis cleanliness among elderly individuals wearing removable dental prostheses. Methods: The sample consists of 382 patients visiting the Dental Outpatient Department of Dhulikhel Hospital for a period of 3 months. The oral examination was conducted using basic diagnostic tools (Mouth mirror, periodontal probe and explorer). A prepared questionnaire was developed regarding oral hygiene habits and also the cleanliness of the removable dental prosthesis and was classified according to the 3-point scoring system for all the subjects. Results: A total of 115 (67.3%) and 63(66.3%) patients above age 50 had kept their prosthesis extremely dirty and dirty in CD and RPD wearers. Patients with low education level had kept their prosthesis extremely dirty [109(73.6%) in CD wearers] and dirty [36(63.2 %) in RPD wearers]. 45(72.6 %) patients wearing RPD at night and 102(75.6 %) patients wearing CD at night had dirty and extremely dirty prosthesis respectively. Factors like age, education, duration of wearing prosthesis, prosthesis worn during night time were associated with prosthesis cleanliness. Similarly, instructions for cleaning prosthesis, method of cleaning and frequency of cleaning had significant association with prosthesis cleanliness. Conclusion: Prosthesis cleanliness was affected by age and education level. Most of the patients were uninformed about the good oral hygiene practices. More information should be provided to the patients for raising the awareness and motivating them in cleaning the denture in order to provide cleaner prosthesis.